Peran Dan Tanggungjwab Notaris Dalam Pendirian Perseroan Terbatas - Dwi Wahyu Diyanto, Indra; Hasanah, Miftahul; Fatimatul Laili, Nur (LPPM Universitas Malikussaleh, 2024)
This research discusses the role and responsibilities of a notary in making a deed of establishment of a Limited Liability Company (PT). The notary functions as the party who has the authority to prepare and ratify the deed of establishment, ensuring that all legal procedures are followed in accordance with the provisions of the applicable regulations. The responsibilities of a notary include verifying the identity of the founder, preparing legal documents, and submitting deeds to obtain approval from the Ministry of Law and Human Rights. Thus, the role of notaries is very crucial in creating legal certainty and protection for PT founders, which essentially aims to support economic stability and development. This research aims to provide a deeper understanding of the roles and responsibilities of notaries in the context of PT establishment in Indonesia.